Sosialisasi Program Keluarga Berencana Dalam Pengendalian Pertumbuhan Penduduk Di Nagari Limau Lunggo - Mutia Merisca Putri; Ata Nashwan Pratama; Nanda Jodi Pratama; Rifky Adlu Ferdiansyah Simatupang; Setiawati Setiawati (CV. ITTC INDONESIA, 2026)
Uncontrolled population growth remains a challenge in various regions, including Nagari Limau Lunggo, Solok Regency. Limited public knowledge regarding the Family Planning (FP) program has contributed to low participation of reproductive-age couples in the use of contraceptives. This study aims to analyze the implementation of FP socialization activities and their impact on increasing community knowledge in controlling population growth.This research employs a descriptive approach using participatory observation, interactive discussions, and counseling for reproductive-age couples (PUS). Data were collected through observation, documentation, and evaluation of participants’ understanding before and after the activities.The results show an improvement in participants’ knowledge regarding birth spacing, contraceptive methods, and the benefits of FP for maternal and child health. In addition, there was a more positive attitude among participants toward consulting health workers before selecting contraceptive methods. This socialization program contributes to increasing public awareness and supports efforts to control population growth at the village level.